2008
DOI: 10.1002/qsar.200710132
|View full text |Cite
|
Sign up to set email alerts
|

3D‐QSAR and Docking Studies of Quinazoline Derivatives with the Inhibitory Activity Toward NF‐κB

Abstract: Nuclear Factor-kB (NF-kB) is an important transcription factor for regulation expression of many cytokines that are involved in the pathogenesis of inflammatory diseases such as Adult Respiratory Distress Syndrome (ARDS), sepsis syndrome, and HIV. It is recently proposed that quinazoline derivatives are capable of inhibiting the activation of NF-kB. To study the inhibiting mechanism and obtain some helpful information for designing functional inhibitor against the protein, 3-D Quantitative Structure -Activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…To further investigate the role of NF- κ B in the modulation of BNP and NPR-1 in BEAS-2B cells after TNF- α treatment, we employed the NF- κ B-DNA binding inhibitor QNZ, which prevents free NF- κ B from binding to DNA [34]. The results obtained with such additional inhibitor, confirmed the previous findings obtained with BAY 11-7082.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…To further investigate the role of NF- κ B in the modulation of BNP and NPR-1 in BEAS-2B cells after TNF- α treatment, we employed the NF- κ B-DNA binding inhibitor QNZ, which prevents free NF- κ B from binding to DNA [34]. The results obtained with such additional inhibitor, confirmed the previous findings obtained with BAY 11-7082.…”
Section: Resultssupporting
confidence: 66%
“…Western blot analysis for the Ser 32 -phosphorylated I κ B- α protein proved the biochemistry evidence of the inhibitory action of BAY 11-7082 on NF- κ B activity ( Figure 3(g) ). To further investigate the role of NF- κ B in the modulation of BNP and NPR-1 in BEAS-2B cells after TNF- α treatment, we employed the NF- κ B-DNA binding inhibitor QNZ, which prevents free NF- κ B from binding to DNA [ 34 ]. The results obtained with such additional inhibitor, confirmed the previous findings obtained with BAY 11-7082.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, different known anti‐inflammatory drugs such as proquazone, fluoroquazone, and tryptanthrin are bearing quinazolinone nucleus (Figure ). Also, it has been reported that some quinazoline derivatives possess potent anti‐inflammatory activity, especially inhibit NF‐κB transcriptional activation . Yet the relationship between anti‐inflammatory activity and structure of quinazoline remains uncertain.…”
mentioning
confidence: 99%
“…Nowadays, comparative molecular field analysis (CoMFA) is a useful technique in understanding the pharmacological properties of studied compounds, because not only CoMFA model is visualized, but also the obtained steric and electrostatic maps may help to understanding the detailed 3D structure of active site of receptor (9–11). Docking analysis is also a useful methodology to further study the action mechanism, as it can offer vivid interaction picture between a ligand and a receptor (12,13).…”
mentioning
confidence: 99%